Estudio bibliométrico de la revista psicooncología (2003-2015) - Morena de Diago, Diego; Morena de Diago, Beatriz (Psicooncología, 2017)
This bibliometric study seeks to present the trajectory of the journal through its 12 years of life. The evaluation shows the production of articles by the number of papers per year, by author, author typology (individual or collective), sex, geographic origin of the authors (countries or autonomous regions), institutional affiliation of the authors, number of signatures in the different articles and, finally, analyze the subjects using the different keywords given by the authors.
Keywords: Bibliometric Analysis; Journal; Bibliometric Indicator; Psycho-Oncology; Cancer.